RAT DENTAL PULP RESPONSE TO PROPOLIS AS A DIRECT PULP CAPPING AGENT - Sabir Ardo (Faculty of Dentistry, Universitas Indonesia, 2006)
The aim of the present study was to assess the response of rat dental pulp to direct pulp capping with ethanol extracts of propolis (EEP). An occlusal cavity was prepared on the right maxillary first molar of Spraque-Dawley rats. The dental pulp was exposed and the lined with a zinc-oxide based filler as a control (group I), or with EEP (group II). Then, each cavity was filled with glass ionomer cement. The animals were sacrificed at week 1, 2, or 4. Biopsy samples were obtained, and these were stained and viewed by a light microscope. The histological examination was based on the presence of polymorph nuclear leukocytes and macrophages, and also the dentinal bridge formation. Data were statistically analysed using Kruskall-Wallis and Mann-Whitney tests. The results showed that the inflammatory response of EEP group was relatively milder compared to the control group, but there was no significant difference (p>0.05) between the two groups. There was no dentinal bridge formation seen in both groups. Therefore, the present results suggest that direct pulp capping with EEP in rats may delay pulp inflammatory process and fail to stimulate reparative dentin.